Optimal layout of sensors in large-span cable-stayed bridges subjected to moving vehicular loads - Qingfei Gao; Kemeng Cui; Jun Li; Binqiang Guo; Yang Liu (International Journal of Distributed Sensor Networks)
To obtain the health status of long-span cable-stayed bridges, multiple sensors are applied to the health monitoring system for data collection. The optimal layout of sensors that aims to obtain as much structural information as possible with fewer sensors is important to ensure the effectiveness of the health monitoring system. Sensors are usually placed in typical locations where the structural response is obvious, and most studies utilize static response for the determination of sensor location. In fact, bridges primarily suffer the dynamic load, of which the response has a significant impact on the structural health. In this article, an optimal sensor layout method for a long-span cable-stayed bridge based on dynamic response is proposed under the consideration of vehicle–bridge coupled vibration. With vehicle load applied onto different lanes, the dynamic responses of different bridge members are obtained, and the number and the location of cable force sensors are determined according to the distribution of cable dynamic coefficient D C , and the number and the location of displacement and strain sensors are determined according to the distribution of D GD and D GM , which are the dynamic load allowance for girder deflection and bending moment, respectively. The results prove that this method can reduce the number of sensors effectively and obtain bridge state information more perfectly.